Approach to management of penile fracture- Our Three-year experience at a Teaching Hospital - Basukala, Sunil; Thapa, Narayan; Rayamajhi, Bikash Bahadur; Basukala, Bikram; Karki, Saurav (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Penile fracture is a rare surgical emergency. It usually occurs as a single rupture of the tunica albuginea in one of the two corpora cavernosa; a rupture of both masses is an uncommon finding. We conducted this study to determine the etiology, clinical presentation and to review the causes and management of penile fracture. Methods: The retrospective study was carried out on 17 patients, admitted in the department of Urosurgery from January 2017 to December 2020 with penile fracture in a tertiary care teaching hospital in Kathmandu. Patient demographic profile, etiology, clinical presentation, time interval from injury to presentation, investigation done, treatment given and intraoperative findings were analyzed. Results: The main cause of penile fractures was sexual intercourse (82.35%) followed by manual manipulation (17.65%). Crackling sound (100%) followed by penile hematoma and pain were the most common presenting symptoms among the patients. Surgical exploration and repair of injury was done in all patients. Conclusion: Most of the time diagnosis of penile fracture can be made reliably by history and physical examination. Early surgical intervention is associated with a good outcome, regardless of the timing of presentation.